An alternative to oxygen deficit as a way to quantify anaerobic contributions in running - Hill, D. W.; Riojas, A. E.; McFarlin, B. K.; Vingren, J. L. (Journal of Human Sport & Exercise, 2019)
The purpose of this study was to determine if the sum of estimates of the phosphocreatine contribution and the glycolytic contribution (we refer to this sum as PCr+glycolysis) provides an alternative to oxygen deficit as a way to quantify the anaerobic contribution in running. Thirty university students performed three treadmill tests, each test at one speed individually selected for each participant; one test was terminated after 3 min, one after 7 min, and one at exhaustion (mean ± SD, 10.3 ± 0.4 min). Oxygen deficit was calculated by subtraction of the accumulated oxygen uptake from the total oxygen cost. Phosphocreatine and glycolysis contributions were determined from post-exercise VO2 responses and blood lactate concentrations, respectively. The mean values for PCr+glycolysis were ~3 mL/kg lower (p < 0.05) than oxygen deficit across three exercise durations, but well correlated (r = 0.80, p < 0.05) at each. These results confirm the validity of PCr+glycolysis as an alternative to oxygen deficit to quantify the anaerobic contribution in running exercise.